Meningkatkan Kemampuan Interaksi Sosial Melalui Bermain Peran Pada Kelompok B Di Tk Aisyiyah Bustanul Athfal Margosari Kecamatan Pagelaran Utara Kabupaten Pringsewu Tahun Pelajaran 2023/2024 - Isti Komariyah; Destri Warni; Jummiati Jummiati (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The background of this study is that the social interaction skills of most students in group B at Aisiyiyah Bustanul Athfal Margosari Kindergarten are still relatively low, this is reflected when there are students seizing the play tools that are being seen by several children. They do not want to take turns to see the playground equipment. In an effort to improve the ability of social interaction, it can be done through the process of learning while playing which makes children feel happy, comfortable, and safe. This research applies the type of classroom action research with data collection techniques of observation and interview techniques, as well as Qualitative data analysis techniques and Quantitative analysis techniques. In the first cycle, the ability of children's social interaction in role playing is 40% capable category, for the second cycle the ability of children's social interaction in role playing is 65% capable category, while the ability of children's social interaction in role playing is 80% capable category. Through role playing, children are expected to develop their social interaction skills, behave according to the guidance of society and be able to adjust to the surrounding environment. Keywords: Social Interaction Ability, Role Play, Classroom Action Research